On Generalized p,q-Euler Matrix and Associated Sequence Spaces - Taja Yaying; Bipan Hazarika; Mohammad Mursaleen (Journal of Function Spaces)
In this study, we introduce new BK-spaces bsr,tp,q and b∞r,tp,q derived by the domain of p,q-analogue Br,tp,q of the binomial matrix in the spaces ℓs and ℓ∞, respectively. We study certain topological properties and inclusion relations of these spaces. We obtain a basis for the space bsr,tp,q and obtain Köthe-Toeplitz duals of the spaces bsr,tp,q and b∞r,tp,q. We characterize certain classes of matrix mappings from the spaces bsr,tp,q and b∞r,tp,q to space μ∈ℓ∞,c,c0,ℓ1,bs,cs,cs0. Finally, we investigate certain geometric properties of the space bsr,tp,q.